2022
DOI: 10.1108/ijwhm-12-2021-0230
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive performance in refugees after trauma: how relevant are post-traumatic stress and post-traumatic growth?

Abstract: PurposeWars can lead to massive migration waves, e.g. the Syrian Civil War that began in 2011 led to the European refugee crisis. Discussions about labour integration often accompany huge spikes in asylum applications. Since many refugees experience traumatic events, such as torture, health problems must be considered in the work context. Unfortunately, the relevance of the post-traumatic experiences of refugees to specific job performance facets has mainly been ignored. To close the research gap, a study with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(154 reference statements)
1
5
0
Order By: Relevance
“…In general, our results are consistent with the data of Cengiz et al (2018), whose regression analysis showed that resilience promoted posttraumatic growth among Syrian refugees. Our results are also consistent with the findings of Eltanamly et al (2022) and Stasielowicz (2022), who confirmed the possibility of personal growth in the civilian population as a result of posttraumatic war experiences.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, our results are consistent with the data of Cengiz et al (2018), whose regression analysis showed that resilience promoted posttraumatic growth among Syrian refugees. Our results are also consistent with the findings of Eltanamly et al (2022) and Stasielowicz (2022), who confirmed the possibility of personal growth in the civilian population as a result of posttraumatic war experiences.…”
Section: Discussionsupporting
confidence: 93%
“…Wars inflict numerous traumas on civilians in countries under attack, including witnessing torture and kidnappings, extreme violence, separation from family and forced migration (Cengiz et al, 2018; Johnson & Thompson, 2008; Stasielowicz, 2022). The consequences of war include negative mental health in the affected population, such as increased rates of anxiety, hostility, depression, posttraumatic stress disorders and dissociative disorders (Bogic et al, 2015; Schlechter et al, 2021; Stasielowicz, 2022; Zasiekina et al, 2022).…”
mentioning
confidence: 99%
“…Similarly to other fields, researchers examining adaptive performance often distinguish between subjective adaptive performance ratings and objective adaptive performance scores (Christian et al, 2017;Stasielowicz, 2019Stasielowicz, , 2020. Subjective ratings are usually collected by asking people to rate their adaptive performance or the performance of others, for example, co-workers or employees (Bohle Carbonell et al, 2014;Stasielowicz, 2022;Stokes et al, 2010). In contrast, people are asked to complete a specific task to measure objective adaptive scores.…”
Section: Adaptive Performancementioning
confidence: 99%
“…The literature is inconclusive regarding the relationship between posttraumatic stress and acculturation. Stasielowicz ( 16 ) studied the adaptive performance of refugees who experienced trauma living in Germany. Adaptive performance refers to “altering behavior to meet the demands of a new situation, event, or set of circumstances” ( 17 , p. 615).…”
Section: Introductionmentioning
confidence: 99%